Desert and Death: Biopolitical Landscapes and Affect in US-Mexico Border Representations - Johannes, Daniela (The University of Arizona., 2015)
This thesis studies the state of current border politics as it can be read through three objects of representation. These correspond to the three chapters. The first deals with a map, read as a text that represents death, made by the Humane Borders organization. The second treats a literary text (2666 by Roberto Bolaño) that also represents death and the border landscape and announces a failure of representation when treating a contemporary horror. The third chapter treats a technological tool thought of as electronic disturbance, designed to help migrants navigate the arduous terrain while crossing to the U.S. On one hand this work is concerned with death at the border as an irreversible fact and also as a matter of representation. Death at the border has been used as a trope to represent migrants and their afflictions (regarded many times as a consequence of ignorance, wildness or uncivilization). It has also been used as part of a political agenda: constructing migrants' illegality and death as a consequence for misconduct. On the other hand, this thesis is concerned with the trope of the desert as the space and a landscape that today is not dissociable from the meanings of death. The analysis takes a discursive angle, but also takes the desert as a material environment, which constitutes a tangible reference in which the practices of sovereignty are carried out. It also considers death as a real, embodied fact. This landscape of death has been marked by the intensification of border control as well as the intensification of humanitarian activism. Indeed, the desert is a site that highlights the precariousness of what is understood to be human life. "The human" moves in and out of being through the interaction of physical political and social elements. This thesis, thus, is concerned with the material and the discursive dimensions that shape the Sonoran Desert as the border between states, between human and non-human matter and as a bordering practice regarding the governance of a population.